Transcervical fibroid ablation with the Sonata™ system for treatment of submucous and large uterine fibroids. Issue 1 (17th March 2021) - Shifrin, Gregory; Engelhardt, Matthias; Gee, Phyllis; Pschadka, Gregor
Abstract: Objective: To examine the role and benefits of transcervical fibroid ablation (TFA) in the treatment of submucous and large uterine fibroids. Methods: A subgroup of patients with submucous or large fibroids were analyzed from two prospective clinical trials (FAST‐EU and SONATA) of sonography‐guided TFA with the Sonata ® system. Key outcomes were changes in menstrual blood loss, symptom severity and health‐related quality of life on the Uterine Fibroid Symptom and Quality‐of‐Life Questionnaire, health‐related quality of life on the EQ‐5D questionnaire, and surgical reinterventions for heavy menstrual bleeding. Results: Among 197 women (534 treated fibroids), 86% of women with only submucous fibroids and 81% of women with large fibroids (>5 cm) experienced bleeding reduction within 3 months post‐ablation. Overall symptom severity and health‐related quality of life showed sustained, significant improvements over 12 months. Additional fibroid mapping of large fibroids with magnetic resonance imaging in the FAST‐EU trial showed an average volume reduction of 68%. Among women with only submucous fibroids, the rate of surgical reintervention through 1 year of follow up was 3.7% in FAST‐EU and 0.0% in SONATA. Conclusion: With the Sonata system, TFA is an effective single‐stage treatment option for non‐pedunculated submucous myomata, and larger or deeper uterine fibroids (including fibroid clusters) for which hysteroscopic treatment is not suitable. ClinicalTrials.gov: FAST‐EU, NCT01226290; SONATA, NCT02228174. Synopsis: Transcervical fibroid ablation with the Sonata™ system is an effective single‐stage treatment option for non‐pedunculated submucous and large myomata.